Effect of Particle Combination Ratio of Soil Rock Mixture on Shear Strength. Issue 1 (1st June 2022) - Li, Shengting; Zhou, Rui; Yang, Fan; Zhang, Yangchun; Du, Yongjun
Abstract: With the increase of fine-grained soil content, the properties continue to transform to fine-grained soil, which will affect the permeability and strength of the soil. Even if the content of silt and clay in fine-grained soil is not high, it will significantly impact soil properties. When the content of coarse particles is low, the nature of soil depends on the fine particles in the soil. When the content of coarse particles gradually increases, and the coarse particles are overhead, the nature of soil only depends on the coarse-grained soil, and the influence of fine particles on the nature of soil gradually weakens. To reveal the interaction mechanism between coarse and fine particles in high moisture content clayey gravel, this project conducts a systematic experimental study on the high moisture content clayey gravel, takes 0.5mm as the particle size limit, takes the separation of coarse and fine particles in the soil sample as the control test, and systematically tests the shear strength of the separated fine particles; systematic shear strength tests were also carried out on the separated coarse particles. In addition, shear strength tests were carried out on soil samples with different fine particle content.